Broadway barks [compact disc, unabridged] - Peters, Bernadette (Blue Apple Books, 2008)
A homeless dog living in a New York City park follows a woman to Broadway Barks, an annual show sponsored by Broadway stars, where he is adopted by a little girl and finds a new home.